Revisiting William James: Religious Experience as Response to Fanaticism in Nigeria - Ndidi Justice Gbule; Christopher Opara (Scriptura Indonesia, 2026)
Religious fanaticism persists as a major challenge in Nigeria, expressed through sectarian violence, doctrinal intolerance, and extremist mobilization. This paper revisits William James’s early 20th-century concept of religious experience, as articulated in The Varieties of Religious Experience, to critically examine its potential and limits for addressing contemporary Nigerian religious tensions. James’s pragmatic philosophy privileges individualized, experiential faith over rigid dogma, yet his framework emerged from a Western, Protestant context over a century ago. To adapt his insights, this study situates James within Nigeria’s pluralistic and postcolonial realities, drawing on contemporary pragmatism, Social Identity Theory, African philosophy of religion, and peacebuilding scholarship. Methodologically, it employs qualitative analysis of Nigerian religious conflicts, extremist texts, and interfaith dialogue initiatives to evaluate the relevance of subjective religious experience in mitigating fanaticism. Findings suggest that, when reinterpreted and integrated with modern conflict-resolution strategies, James’s approach can inform educational, policy, and interfaith practices that privilege empathy, critical reflection, and mutual understanding. The study concludes by recognizing the limitations of applying James’s theory in isolation, but proposes a hybrid philosophical framework for fostering tolerance and peaceful coexistence in Nigeria’s multi-religious society.